2017
DOI: 10.1590/1807-2577.00117
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of mandibular retromolar canals on cone beam computed tomography and its clinical repercussions

Abstract: ResumoIntrodução: O conhecimento da morfologia normal da mandíbula humana e suas possíveis variações anatômicas, que ocorrem, são de fundamental importância na prática odontológica, especialmente nas áreas da cirurgia e implantodontia. A região retromolar é delimitada pela margem anterior do ramo da mandibular, crista temporal e face distal do último molar inferior. Nessa área pode ser observado o canal retromolar que pode emergir pelo forame retromolar. Objetivo: O presente estudo objetiva avaliar a ocorrênci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
(34 reference statements)
3
11
0
Order By: Relevance
“…When observing the relative frequency of mandibular canal bifurcation according to its classification in the present study, class D (retromolar direction) was the most prevalent with 39.1% of cases of mandibular canal bifurcation. Freitas et al 17 found a prevalence of 19.4% of retromolar bifid canals in their study. The second most prevalent classification was class C (alveolar direction), which occurred in 21.7%.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…When observing the relative frequency of mandibular canal bifurcation according to its classification in the present study, class D (retromolar direction) was the most prevalent with 39.1% of cases of mandibular canal bifurcation. Freitas et al 17 found a prevalence of 19.4% of retromolar bifid canals in their study. The second most prevalent classification was class C (alveolar direction), which occurred in 21.7%.…”
Section: Discussionmentioning
confidence: 66%
“…The sample was divided into 3 groups according to facial types: CT scans were all obtained from the I-Cat  (Imaging Science, Hatfield, PA) equipment with Fov 20 cm, voxel 0.25 mm and 20s, Kvp120 and 36mA. The sample size was based on previous recently published studies [16][17][18] .…”
Section: Methodsmentioning
confidence: 99%
“…Results in the current study were analyzed and tabulated using the Statistical Package for Social Science (SPSS) software as described by Freitas et al for their statistical analysis [27]. Intra-reviewer analysis and inter-reviewer analysis were done to determine the reliability of measurements, frequencies, and percentages to find the percentage of RMF in the sample, and χ 2 (chi-square test) and Fisher's exact test were calculated to identify the significant incidence.…”
Section: Discussionmentioning
confidence: 99%
“…It is quite obvious that there is a vast difference between the incidence rate reported in panoramic studies due to the limitation of being a 2D modality and CBCT studies; several studies have reclaimed incidence rates of 3-8% [14,23,28] and 7.3-75.4% [5,27] in panoramic and CBCT studies, respectively. 11.2% was reported in this study which falls in the range of the previously reported studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation